From Citizen Ideology to Netizen Ideology: The Legal Culture of Digitizing Pancasila in Realizing Politeness on Social Media - Indrayani, Kiki; Sulaksono, S.; Tamsil, T.; Prasetio, Dicky Eko (Manunggal Halim Jaya, 2024)
This study aims to analyze the reconstruction of Pancasila ideology within the virtual space: from citizen ideology to netizen ideology, and the cultural orientation of digital Pancasila in fostering civility in Indonesian social media. This research is a socio-legal study that emphasizes a literature review and qualitative analysis. The findings underscore that a reconstruction of understanding and education on Pancasila is necessary to ensure its application aligns with contemporary developments. The cultural orientation of digital Pancasila in promoting social media civility can be achieved through digital Pancasila education, which produces influencers among Indonesian netizens committed to implementing Pancasila values on social media, and through the establishment of a Pancasila digital society network.